Post-war Britain : a political history - Sked, Alan; Cook, Chris (London : Penguin Books, 1993)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Thatcher, Margaret; Labour Party (Verenigd Koninkrijk).; Churchill, Winston; Groot-Brittannië.